Penguatan Pemahaman Mahasiswa Terhadap Peran Ombudsman Dalam Pelayanan Publik Di Fakultas Ilmu Sosial Universitas Negeri Makassar - Andi Muhammad Rivai; Yusi Irensi Seppa; Sitti Syarifah Wafiqah Wardah; Andi Tenri Ola Rivai; Andi Akram Nur Risal (Vokatek: Jurnal Pengabdian Masyarakat, 2023)
This Student Creativity Program (PKM) aims to increase the understanding of students of the Faculty of Social Sciences at Makassar State University about the role of the Ombudsman in public services. With a focus on training and interactive activities, the PKM aims to provide an in-depth understanding of the role of the Ombudsman as well as optimal ways of monitoring and supervision related to public services. Before the PKM, only 40% of students understood the role of the Ombudsman. After participating in PKM activities, students' understanding increased significantly to 75%. This result reflects the positive impact of PKM on increasing students' awareness of the role of the Ombudsman. Students also appreciated this activity, considering it very useful for increasing the role and supervision of the Ombudsman in public services. Thus, this PKM not only contributed to students' understanding but also taught them to participate in ensuring the quality of public services through the role of the Ombudsman.